Evaluation of the Efficacy of Surgical Treatment of Patients With Chronic Critical Ischemia of Lower Extremities at the Stage of Trophic Complications - B. V. Kozlovsky; I. P. Mikhailov; G. A. Isayev; N. E. Kudryashova; O. V. Leshchinskaya (Неотложная медицинская помощь)
Relevance. Chronic critical ischemia of the lower extremities (CCILE) in the stage of trophic complications is the final stage of diseases of the arteries of the lower extremities, leading to disability of patients and having a poor prognosis in terms of preservation of the lower extremities and mortality.Aim of study. Objective assessment of the efficacy of lower limb revascularization in trophic disorders.Material and methods. The analysis of treatment of 52 patients with stage IV CCILE (according to the classification of R. Fontaine and A.V. Pokrovsky) was carried out. Of these, 42 patients underwent three-phase scintigraphy combined with X-ray computed angiography on a hybrid apparatus. After the operation, this study was conducted in 37 patients.Results. Out of 52 patients, surgery for revascularization of the lower extremities was performed in 37 patients, 15 were not operated on. Out of 37 operated patients, improvement of blood circulation occurred in 32 (86.5%). Circulatory decompensation was observed in 5 patients (9.7%). Among non-operated patients, improvement of blood circulation occurred in 9 patients (17.3%), no effect or decompensation — in 5 (9.7%). Subjective improvement in the condition and decrease in the degree of ischemia corresponded to the improvement of microcirculation according to the data of three-phase scintigraphy.Conclusion.1. Revascularization of the lower extremities in patients with trophic disorders is an effective method of treating this pathology. Therefore, all patients with chronic ischemia threatening limb loss should be considered as candidates for revascularization.2. If the leg arteries or short occlusive or stenotic lesions of the main arteries are affected, such patients should be discussed together with specialists in endovascular surgery for endovascular treatment or joint intervention.3. Hybrid radiation method (three-phase scintigraphy and single-photon emission computed tomography, combined with X-ray computed angiography) is an objective method that reflects the state of peripheral circulation and microcirculation, and allows you to objectively assess the effectiveness of the treatment.